Analisis Service Quality (ServQual) pada AMIK Mahaputra Riau - Rachmad, Ferizal (Basecamp Economics PubMed, 2024)
The purpose of this research is to determine the factors that influence service quality and to find out what factors most dominantly influence service quality at AMIK Mahaputra Riau. The sample for this research used the census method, namely the entire number of AMIK Mahaputra Riau students in 2020, namely 180 students Simultaneously, the Reliability, Tangible, Assurance, Emphaty and Responsiveness factors influence the service quality of AMIK Mahaputra Riau. This conclusion is supported by the truth from the analysis results which prove that f-count = 48.365> f-table = 2.32. Apart from that, the Reliability, Tangible, Assurance, Emphaty, Responsiveness factors are able to explain AMIK Mahaputra Riau's service quality of 72.7%, this can be seen of the terminated coefficient value R2 = 72.7% the remaining 27.3% is explained by factors other than Reliability, Tangible, Assurance, Empathy, Responsiveness. Of all the independent variables studied, it turns out that the variable that has the most dominant influence on service quality at AMIK Mahaputra Riau is the Tangible variable. This conclusion was proven to be correct based on the results of statistical analysis using the t-test where t-count = 10.787> t-table = 1.989 with a significance of 0.000.